50 science things to make and do - Knighton, Kate; Andrews, Georgina Baggott, Stella (Usborne Publishing Ltd china, 2008)
These cards bring a fresh and exciting approach to the practical world of science, combining creative arts and crafts activities with the basics of physics, chemistry and biology. This title contains 50 stimulating and original activities, including foaming monsters, hanging crystals and kaleidoscopes. Each activity is safe and simple to carry out using the step-by-step instructions and uses objects and materials that can be easily found. The cards are durable and robust, making them ideal for repeated use.